THE FINANCIAL INTERMEDIARIES, A REAL DANGER FOR BANKS? - Zapodeanu Daniela; Popa Diana (Annals of the University of Oradea: Economic Science, 2008)
The presence of the financial intermediaries - that make the link between the economics agents, with the needs of resources and the one with surplus of resources - determinates the evolution of the banking system and the structure modification of these. What is the difference between a bank and a financial intermediary? The bank distinguish itself from the financial intermediary through its capacity of taking inside the costs and its informatic efficiency, and so the incomes are growing. Does the financial intermediaries represents a danger for the banks?